Aleutian Campaign, World War II: Historical Study and Current Perspective. - Johnson, Robert L. (1992)
This work is a detailed historical study of the Aleutians Campaign conducted by U.S. Armed Forces from 3 June 1942 through 18 August 1943 to gain control of the North Pacific and eject the Japanese from Attu and Kiska Islands. The campaign, characterized by combined and joint operations, involved an extended air battle, a brutal fight for control of the waters of the western Aleutians, and two major combat amphibious operations. The Aleutians Campaign, of major significance at the time, quickly became over-shadowed by later naval, air, and amphibious operations conducted in the Pacific. Though studied extensively after August 1943 to apply lessons learned to other operations, the Aleutians Campaign attracted little attention by military scholars in the years after World War II. This study details the conduct of the campaign and applies tactical, operational, and strategic aspects to the current U.S. Army model for campaign planning.